Determinan yang Mempengaruhi Perilaku Merokok Elektrik Pada Siswa Sekolah Menengah Atas Negeri (SMAN) Se-Kota Jambi - Mhd Fathul Rozi; M. Ridwan; M. Rifqi Azhary; Puspita Sari; Vinna Rahayu Ningsih (Poltekkes Kemenkes Jambi, 2025)
Background: The use of electronic cigarettes (vapes) is increasingly prevalent among adolescents, including high school students. E-cigarettes are often perceived as safer than conventional cigarettes, although they still contain harmful substances such as nicotine and formaldehyde. This study aimed to determine the determinants influencing electronic cigarette smoking behavior among high school students in Jambi City. Methods: This quantitative study employed a cross-sectional design involving 96 respondents selected through proportional random sampling. Data were collected using questionnaires and analyzed using the Chi-Square test (α = 0.05). Results: A total of 68.9% of students reported using electronic cigarettes. There were significant associations between smoking history (p = 0.000), perception (p = 0.002), accessibility (p = 0.019), pocket money (p = 0.005), and media exposure (p = 0.004) with electronic cigarette use behavior. However, no significant relationships were found with parental influence (p = 0.966), teacher influence (p = 0.179), or peer influence (p = 0.219). Conclusion: Predisposing and enabling factors such as smoking history, perception, and accessibility play a crucial role in adolescents’ electronic cigarette use behavior. Education, family supervision, and regulation of e-cigarette access are necessary to reduce usage among teenagers.